A comparative study on the accessibility of microcredit and gloan of selected microbusinesses in Manila for Q2-Q4 of 2022 affecting financial performance - Barrozo, Laarni Mae S., De Jesus, Kim Dorothy Kristian E., Dela Cruz, Danese Anne, Legaspi, Alliyah Fatima E., Sosas, Anne Kristine L., Tengson, Ma. Cristina Angela G. 4 0 16; 5 (2023)
Abstract This study focuses on the accessibility of these microbusinesses in Microcredit by banks and GLoan as their source of credit to which affects their financial performance during Q2-Q4 of 2022 in Manila, specifically in Dragon 8 Mall in Divisoria Market located in Tondo, Manila. Microbusinesses in the Philippines play a big role in the economy, bringing growth in our economy because this has the majority percentage of Micro, Small, and Medium Enterprises in the country. As for this, these microbusinesses generate more opportunities available in the market, but the opportunities for these microbusinesses are limited as one of as its core problems is its accessibility to credit facilities in the country. Furthermore, the Microcredit by banks and GLoan are credit facilities that bring these microbusinesses the ability for them to expand their businesses to which can bring more goods, services, and/or expand their vicinity in the market. The researchers applied a comparative research design which aims to compare Microcredit by banks and GLoan, as Microcredit by banks had long been established compared to GLoan, which was established in 2022. This study sets the comparison in terms of the micropreneurs' level of accessibility and level of preference to these two credit facilities being compared in this study. As for the Statement of the Problem of this study, the first problem is knowing the classification and characteristics of the microbusiness in terms of: MSME classification as to asset size and number of employees, type of trading business, number of years operating the microbusinesses, credit facility commonly tap, number of years acquiring loan from Microcredit and GLoan, and highest borrowed amount from Microcredit and GLoan. The second problem focuses on the level of accessibility of Microcredit and GLoan in terms of: loan rate, loan tenure, loan requirements, loan procedure, and loan payment facility. The third problem focuses on the level of preference on Microcredit and GLoanas a source of credit of the respondents. After knowing these problems in the comparison of these two credit facilities, the last problem in this study is knowing the level of financial performance of the microbusinesses for Q2-Q4 of 2022 according to their net profit as a set financial metrics and key performance indicators. For the researchers to be able to get data and information about these problems, they used a self-made questionnaire to which a 4-point Likert scale is applied. After gathering the data from its respondents, the researchers applied statistical treatment to it such as frequency, percentage, and t-test to which the raw data that the researchers gathered run through the software called Statistical Package for the Social Sciences (SPSS). 2From the findings and results of this study, the researchers concluded that there is a significant difference between Microcredit and GLoan as its hypothesis. Additionally, through the applied theory of this study, 'The Theory of Change for Microcredit', it has concluded that the loan that they got from these credit facilities had uplifted the standard of living of these micropreneurs. This is through the effect of Microcredit by banks and GLoan on the financial performance in terms of net profit of these microbusinesses in Dragon 8 Mall in Divisoria Market.
Undergraduate Thesis: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2